Paralympic athlete`s health - Van de Vliet, P. (British Journal of Sports Medicine, 2012)
While sport has value in everyone's life, it is even more important in the life of a person with a disability. This is because of the rehabilitative influence sport can have, on the physical body, and on rehabilitating into society. Nowadays, sports and physical activity found its way in rehabilitation, and individuals with a disability participate in high-performance as well as in competitive and recreational sport across the world. The Paralympic Games, originated from sports complementary to physical rehabilitation, are the pinnacle event.1